The long-term effects of in-work benefits in a life-cycle model for policy evaluation - Richard Blundell; Monica Costa Dias; Costas Meghir; Jonathan Shaw (Centre for Microdata Methods and Practice (cemmap), 2011)
This paper presents a life-cycle model of woman's labour supply, human capital formation and savings for the evaluation of welfare-to-work and tax policies. Women's decisions are formalised in a dynamic and uncertain environment. The model includes a detailed characterisation of the tax system and of the dynamics of family formation while explicitly considering the determinants of employment and education decisions: (i ) contemporaneous incentives to work, (ii ) future consequences for employment through human capital accumulation and (iii) anticipatory effects on the value of employment and education. The choice of parameters follows a careful calibration procedure, based of a large sample of data moments from the British population during the nineties using BHPS data. Many important features established in the empirical literature are reproduced in the simulation exercises, including the employment effects of the WFTC reform in the UK. The model is used to gain further insight into the responses to two recent policy changes, the October 1999 WFTC and the April 2003 WTC/CTC reforms. We find small but non-negligible anticipation effects on employment and education.
Keywords: 330; Weibliche Arbeitskräfte; Arbeitsangebot; Lebensverlauf; Humankapital; Steuerpolitik; Großbritannien